1984
DOI: 10.1017/s0043174500059014
|View full text |Cite
|
Sign up to set email alerts
|

Early Preplant Herbicide Applications for No-Till Soybean (Glycine max) Weed Control

Abstract: Several field studies were conducted during 1981 and 1982 to determine whether early preplant (EPP) applications of residual herbicides would prevent the establishment of vegetation before planting no-till soybeans [Glycine max(L.) Merr. ‘Williams’]. Early preplant applications of either cyanazine {2-[[4-chloro-6-(ethylamino)-s-triazin-2-yl] amino]-2-methylpropionitrile} or cyanazine plus oryzalin (3,5-dinitro-N4,N4-dipropylsulfanilamide) were applied in the fall and 3, 2, and 1 month(s) before planting no-til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 4 publications
(6 reference statements)
6
59
1
Order By: Relevance
“…Fall panicum and prickly sida control were similar with EP and PRE herbicide applications. Our results agree with those ofStougaard et al (16) in that EP applications cannot provide adequate season-long control of fall panicum where densities are high. Pennsylvania smartweed control was greater with EP than with PRE applications.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Fall panicum and prickly sida control were similar with EP and PRE herbicide applications. Our results agree with those ofStougaard et al (16) in that EP applications cannot provide adequate season-long control of fall panicum where densities are high. Pennsylvania smartweed control was greater with EP than with PRE applications.…”
Section: Discussionsupporting
confidence: 89%
“…The soil-applied herbicide oryzalin applied prior to wheat maturity has provided adequate residual control of some summer annual weeds in continuous wheat (I). Stougaard et al ( 16) found oryzalin…”
mentioning
confidence: 99%
“…Moreover, NT could promote weed germination and growth since there is no soil inversion. Several previous studies observed higher weed proliferation and diversity in NT than conventional tillage (Stougaard et al 1984;Kettler et al 2000;Légère et al 2008), and thus weed control became one of the main problems under NT (Soane et al 2012;Melander et al 2013;Nichols et al 2015). Weed competition would adversely affect crop root growth (Norris 1992;Rajcan and Swanton 2001;Silva et al 2011;Rizzardi and Wandscheer 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Fall applications of residual herbicides have been reported to provide excellent control of winter annual weeds (Hasty et al 2004;Stougaard et al 1984). Fall-applied residual herbicides are commonly recommended in Mississippi for management of GR horseweed [Conyza canadensis (L.) Cronq.]…”
mentioning
confidence: 99%